Aluminum Leachability Evaluation from Oven Dried Alum Sludge - Mohammed Zaboon, Sami (Iraqi Journal of Chemical and Petroleum Engineering, 2011)
Phosphorus and dye (direct black) removal for small – scale wastewater applications were investigated using oven dried alum sludge (ODS).The use of alum sludge not only provides a low cost technique but also reduces the hazard and the cost related to the disposal of large amount of alum sludge. Phosphorus and dye removal exceeds 90% for all operating conditions applied in the research.The residuals generated during the treatment of wastewater were further tested to study the possibility of aluminum leaching from oven dried alum sludge during the adsorption of phosphorus and dye. These tests observed a reduction in aluminum leaching indicating a lower risk imposed on land and surface water based on disposal options rather than on alum sludge disposal.The leaching of aluminum was observed to be mostly below 1 mg/l for a pH solution of 6 and 7 for both processes of phosphorus and dye removal. However, the pH of 5 seemed to have a concentration of more than 1mg/l of aluminum.